Using Early Exam Results to Predict Online MLS Program Success. (9th November 2022) - Robertson, C; Johnson, N; Bird, R; Key, J
Abstract: Introduction/Objective: The objective of this effort is to demonstrate the impact of early didactic exam results for potential early intervention for students in an online medical laboratory science bridge program. Methods/Case Report: For this study, we took retrospective data of 299 students from 2018 to 2021 who took MLSC 4312, Hematology, in their first semester. We then analyzed their first exam score and then used this data to evaluate its potential use as an early predictor of overall student success in both this course and the program. Specifically, the exam one score in the course was used to evaluate progression to the second semester, graduation, UAMS GPA, and ASCP Board of Certification total score and Hematology sub-score. Descriptive statistics and 2-sample T-tests were calculated using Number Cruncher Statistical System. Fisher's exact test was performed using Graphpad software. Results (if a Case Study enter NA): Of the 296 students whose records were examined, 49 scored below a 76% on Hematology exam 1. 247 students scored above 75%.35 students who scored below 76% progressed to the second semester and of those, 33 (94.2%) graduated on time. 14 students were dismissed from the program after the first semester. The overall graduation rate of students who started the program and scored less than 76% on the first hematology exam was 67%. Of the 247 students who scored above 76% on exam 1, 229 (93%) progressed to the second semester and of those, 214 graduated on time (93.4%). 18 of these students were dismissed from the program. The overall graduation rate of students who started the program and scored greater than 76% on the first hematology exam was 86.70%. The overall ASCP Board of Certification pass rate was almost 19 percent higher, 81.7% vs. 62.9% in those who scored greater than 76% on the first hematology exam. Each of the comparisons was statistically significant (P=<0.05) using a 2-sample T-test or Fisher's exact test as appropriate. Conclusion: This study revealed the importance of doing well on the first major didactic exam in the Medical Laboratory Sciences program. Students who score < 76% on their first exam fail to progress to the second semester at four times the rate of those who score >76%. In addition, those who score <76% and progress fail the ASCP Board of Certification Exam at almost double the rate of those who score >76% on the first hematology exam. In the future, we will reach out earlier and offer targeted help to these students.